2017
DOI: 10.3389/fmicb.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

MLVA Genotyping Characteristics of Human Brucella melitensis Isolated from Ulanqab of Inner Mongolia, China

Abstract: Brucellosis is a serious public health problem in Ulanqab, which is a region located in the middle of the Inner Mongolia Autonomous Region adjacent to Shanxi and Hebei provinces. The disease is prevalent in both the latter provinces and Ulanqab with the highest prevalence of brucellosis occurring in Inner Mongolia. The MLVA-16 scheme is a genotyping tool for assessing genetic diversity and relationships among isolates. Moreover, this genotyping tool can also be applied to epidemiological trace-back investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 32 publications
5
52
0
Order By: Relevance
“…There were at least two alleles for each of the 16 loci investigated by the MIVA approach, which is different from the results of studies of B. melitensis diversity in China. For B. melitensis , the Bruce06, Bruce08, Bruce11, Bruce12, Bruce42 and Bruce45 loci of panel 1 and the Bruce18 locus of panel 2A each showed only one allele (HGDI = 0), and the Bruce04 locus displayed the highest diversity (Liu et al, ). Similarly, Jianghai et al reported that both Bruce16 and Bruce30 in the panel 2B markers were most useful for typing B. melitensis strains from China (H. Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There were at least two alleles for each of the 16 loci investigated by the MIVA approach, which is different from the results of studies of B. melitensis diversity in China. For B. melitensis , the Bruce06, Bruce08, Bruce11, Bruce12, Bruce42 and Bruce45 loci of panel 1 and the Bruce18 locus of panel 2A each showed only one allele (HGDI = 0), and the Bruce04 locus displayed the highest diversity (Liu et al, ). Similarly, Jianghai et al reported that both Bruce16 and Bruce30 in the panel 2B markers were most useful for typing B. melitensis strains from China (H. Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus variable‐number tandem‐repeat analysis‐11 of 66 isolates found a novel genotype (genotype 369: 1‐5‐3‐13‐2‐2‐3‐2‐7‐41‐8), which emerged in panel 2B when the isolates were compared with other strains from different regions in China (Liu et al., ; Tian et al., ). The analysis indicated a dominant Brucella genotype that was relatively stable, but variations emerged in panel 2B within the bruce04, bruce16 and bruce30 loci.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lower genetic diversity and crowding effects may favour transmission and select for faster replicating organisms with major zoonotic potential (Moreno, ). Therefore, the epidemic of brucellosis in animals may increase the prevalence of extensive cases, especially with a massive outbreak in Inner Mongolia, threatening thousands of people (Hou et al., ; Liu et al., ). Furthermore, comparing the 66 isolates from this study with 600 strains isolated from different animals and humans throughout China indicated that animal brucellosis exhibited almost the same epidemiological characteristics in different regions, suggesting these strains may be epidemiologically linked (Tian et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations